Civilizational imperatives Americans, Moros, and the colonial world - Charbonneau, Oliver 1984- (Ateneo de Manila University Press, 2021)
In Civilizational Imperatives, Oliver Charbonneau reveals the little-known history of the United States' colonization of the Philippines' Muslim South in the early twentieth century. Often referred to as Moroland, the Sulu Archipelago and the island of Mindanao were sites of intense US engagement and laboratories of colonial modernity during an age of global imperialism.